2017
DOI: 10.1002/ceat.201600145
|View full text |Cite
|
Sign up to set email alerts
|

Compression Testing and Modeling of Spherical Cells – Comparison of Yeast and Algae

Abstract: The yeast Saccharomyces cerevisiae and the microalga Chlorella vulgaris were mechanically characterized using single‐cell compression experiments. Micromechanical cell characteristics could be calculated directly from the force displacement data. The mechanical properties of the cell wall were determined with different analytical models because the intrinsic parameters of the cell wall cannot be measured directly. As expected, the Young's moduli obtained from the cellular model and the cell wall model differ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Therefore, if the primary mode of deformation is stretching, the bending energy can be neglected, simplifying the model. Similar assumptions have been adopted in the model by Overbeck et al [20] and are common in liquid drop models [18].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, if the primary mode of deformation is stretching, the bending energy can be neglected, simplifying the model. Similar assumptions have been adopted in the model by Overbeck et al [20] and are common in liquid drop models [18].…”
Section: Resultsmentioning
confidence: 95%
“…The first segment is in contact with the spherical indenter, and its radius equals R0. The size of the segment is given by the radius distance a, defined as follows: (6) The principal curvatures of the first segment, and , are both equal to 1/R0. The curvature of the second arc is denoted as R1.…”
Section: Fig 1 Geometry Of Spherical Afm Tip and Membrane Interactionmentioning
confidence: 99%
“…However, in this study, the 90% value of the cumulative SE distribution was used to calculate . Nevertheless, excessive normal forces can also cause individual cells to burst ( Taubert et al, 2000 ; Günther et al, 2016 ; Overbeck et al, 2017 ). Furthermore, Dittmann et al (2019) , suggested that pellet compression may alter the internal pellet structure due to plastic deformation or cell adhesion effects.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, liposomes adhered to the surface considerably and were excluded from the analysis. Overbeck et al, 2017 showed that, in addition to cell size, osmotic pressure could affect cell response, where higher osmolarity of the culture contributes to a decrease in cell stiffness .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we will address one particular effect, cell size. Although theoretical and experimental cell studies based on elastic shell theory [33] and liquid drop theory [23] suggest that cell stiffness is considerably affected by its dimensions, it is neglected in Hertz theory. We hypothesized that larger cells will have a smaller stiffness and therefore a smaller Young's modulus, and vice versa.…”
Section: Introductionmentioning
confidence: 99%